Pengaruh Komitmen Organisasi dan Kepuasan Kerja melalui Motivasi terhadap Kinerja Karyawan pada PT. Bank Pembangunan Daerah Jambi Kantor Cabang Sutomo - Muhammad Iqbal Wendry; Arna Suryani; Sudirman Sudirman (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to describe and analyze the influence of organizational commitment and job satisfaction on employee performance—both directly and indirectly through motivation—among employees at the Sutomo Branch of Bank Jambi (Regional Development Bank of Jambi). The research variables include organizational commitment, job satisfaction, motivation, and employee performance. The study population consists of all 55 permanent employees at the Bank Jambi Sutomo Branch; consequently, a census sampling technique was employed. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that organizational commitment and job satisfaction have a positive and significant effect on work motivation. Organizational commitment has a positive and significant effect on employee performance, whereas job satisfaction does not have a significant direct effect on employee performance. Furthermore, motivation has a positive and significant effect on employee performance. This implies that motivation mediates the influence of organizational commitment and job satisfaction on employee performance. Thus, motivation serves as a crucial factor in enhancing employee performance at the Bank Jambi Sutomo Branch.